Titania‐Supported Catalysts for Levulinic Acid Hydrogenation: Influence of Support and its Impact on γ‐Valerolactone Yield. Issue 9 (14th January 2015) - Ruppert, A. M.; Grams, J.; Jędrzejczyk , M.; Matras‐Michalska, J.; Keller, N.; Ostojska, K.; Sautet, P.
Abstract A series of titania‐supported ruthenium and platinum catalysts was investigated in the levulinic acid hydrogenation towards γ‐valerolactone, a key reaction for the catalytic transformation of biomass. It was shown that various morphologies and phases of titania strongly influence the physicochemical and catalytic properties of supported Ru and Pt catalysts in different ways. In the case of the catalyst supported on mixed TiO2 phases, Ru particles are exclusively located on the minority rutile crystallites, whereas such an effect was not observed for platinum. The platinum catalyst activity could be increased when the metal was dispersed on the large surface‐area anatase, which was not the case for ruthenium as a result of its agglomeration on this support. The activity of ruthenium on anatase could be increased in two ways: a) when RuO2 formation during catalyst preparation was avoided; b) when pure anatase support material was modified so that it exhibited no microporosity. The obtained results allow a better understanding of the role of the support for Ru and Pt catalysts.